Revision of Conception of Gradual Formation of Actions for Education and Psychological Development - Solovieva, Yulia; Quintanar, Luis (Frontiers in Psychology, 2020)
Psychological conception of formation of action by stages is one of the most significant contributions of activity theory. This conception might be understood in two ways: 1) in a broad way as general psychological conception and 2) in a straight way as conception of the process of teaching and learning according to activity theory. We propose to consider the union of these two conceptual possibilities as a general methodological proposal for the study of development. The article offers a revision of conception of gradual formation of action by stages according to modern educational needs in the sense of establishment of union between Vigotsky’s and Galperin’s conception of psychological development. The article revises the possibility for usage of this methodology in a broad way as a general psychological conception, which might include modes of positive development together with developmental difficulties. From the point of view of activity theory approach, brain functional systems might be understood as psycho-physiological dynamic mechanisms of actions and operations fulfilled by a subject. At the same time, the subject’s own action is always accomplished within the context of one or another cultural activity. Conception of gradual formation of action by stages helps to plan and organize specific types of interaction between child and adult in significant cultural situations. The stages of formation of cultural action, discussed in the article, are: material action with objects, materialized actions with external symbols, perceptive concrete action with concrete images, perceptive symbolic action with perceptive symbols and verbal actions. Orientation base of action is essential part of action on each level. These stages differ from original proposal within Galperin’s theory and offer a possibility of work with different kinds of actions: practical, intellectual, artistic and physic actions. All these types of actions might be used in educational processes in optimal situations and in situations with developmental difficulties. Our proposal opens the question about types of actions, which might be considered during formation process, such as practical and intellectual actions. We discuss the usefulness of this psychological conception for the methods of assessment, correction and teaching, which conduct to development of the child.